Nucleocytoplasmic partitioning of tobacco N receptor is modulated by SGT1. Issue 1 (3rd June 2013) - Hoser, Rafał; Żurczak, Marek; Lichocka, Małgorzata; Zuzga, Sabina; Dadlez, Michal; Samuel, Marcus A.; Ellis, Brian E.; Stuttmann, Johannes; Parker, Jane E.; Hennig, Jacek; Krzymowska, Magdalena
Summary: SGT1 (S uppressor of G2 allele of SKP1) is required to maintain plant disease R esistance (R) proteins with N ucleotide‐B inding (NB) and L eucine‐R ich R epeat (LRR) domains in an inactive but signaling‐competent state. SGT1 is an integral component of a multi‐protein network that includes RACK1, Rac1, RAR1, Rboh, HSP90 and HSP70, and in rice the M itogen‐A ctivated P rotein K inase (MAPK), OsMAPK6. Tobacco ( Nicotiana tabacum ) N protein, which belongs to the T oll‐I nterleukin R eceptor (TIR)‐NB‐LRR class of R proteins, confers resistance to T obacco M osaic V irus (TMV). Following transient expression in planta, we analyzed the functional relationship between SGT1, SIPK – a tobacco MAPK6 ortholog – and N, using mass spectrometry, confocal microscopy and pathogen assays. Here, we show that tobacco SGT1 undergoes specific phosphorylation in a canonical MAPK target‐motif by SIPK. Mutation of this motif to mimic SIPK phosphorylation leads to an increased proportion of cells displaying SGT1 nuclear accumulation and impairs N‐mediated resistance to TMV, as does phospho‐null substitution at the same residue. Forced nuclear localization of SGT1 causes N to be confined to nuclei. Our data suggest that one mode of regulating nucleocytoplasmic partitioning of R proteins is by maintaining appropriate levels of SGT1 phosphorylation catalyzed by plant MAPK.